2022
DOI: 10.1101/2022.03.28.486145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive profiling of antibody responses to the human anellome using programmable phage display

Abstract: Viruses belonging to the diverse Anelloviridae family represent a major constituent of the commensal human virome. Aside from their widespread prevalence and persistence in humans and their absence of detectable pathologic associations, little is known about the immunobiology of the human anellome. In this study, we employed the Phage ImmunoPrecipitation Sequencing (PhIP-Seq) assay for comprehensive analyses of antibody binding to 56 amino acid long anellovirus peptides. We designed and constructed a large and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…These results suggest that proteolysis of the ORF1 C-terminus may be a natural part of anellovirus formation. In light of recent evidence that the C-terminal region of ORF1 is the immunodominant region of anelloviruses 16 , its excision from the mature particle would be consistent with the immune evasion properties of anelloviruses 17 . Further exploration of the role of the C-terminal region of ORF1 will help clarify its importance in the anellovirus life cycle.…”
Section: Anellovirus Ly1 Orf1 Fragment Structurementioning
confidence: 60%
“…These results suggest that proteolysis of the ORF1 C-terminus may be a natural part of anellovirus formation. In light of recent evidence that the C-terminal region of ORF1 is the immunodominant region of anelloviruses 16 , its excision from the mature particle would be consistent with the immune evasion properties of anelloviruses 17 . Further exploration of the role of the C-terminal region of ORF1 will help clarify its importance in the anellovirus life cycle.…”
Section: Anellovirus Ly1 Orf1 Fragment Structurementioning
confidence: 60%
“…We used this technology to demonstrate in a blood-transfusion cohort that anelloviruses can be transmitted from donors and can persist for at least nine months in recipients 14 . Recently, we used a phage immunoprecipitation sequencing (PhIP-Seq) assay to comprehensively profile antibody responses to the human anellome 52 . In this study, we introduce an in vitro system for the production of human anelloviruses, which will enable further basic research into anelloviruses, the knowledge from which can be used to develop anellovirus-based gene therapies.…”
Section: Discussionmentioning
confidence: 99%
“…All specific criteria for annotation are listed in Table S7 . Sequence motifs were identified using OrfM ( 68 ), following the protocols of Arze et al ( 11 ) and Venkataraman et al ( 29 ), with the following parameters: print stop codons (-p), print ORFs in the same frame as stop codon (-s), and including ORFs longer than 49 amino acids (-m 150). Specific ORFs were subsequently filtered using seqkit (seq and grep function) using the following parameters: search sequence data (-s), enable regex pattern searching (-r), search for specific length (-m), and specific motif (-p).…”
Section: Methodsmentioning
confidence: 99%
“…Because higher anellovirus titers are found in immunocompromised patients ( 25 28 ), it is likely that anellovirus loads are partly regulated by the host immune system. Recent findings based on AnelloScan (T7 phage display anellovirus peptide library immunoprecipitation assay) showed that anellovirus proteins elicit varied antibody reactivity ( 29 ). Reactivity was mainly observed against the C-terminal region of ORF1.…”
Section: Introductionmentioning
confidence: 99%